Taking a cellular road-trip: mRNA transport and anchoring - Pratt, Catherine A. (2012)
mRNA localization is a crucial mechanism for post-transcriptional control of gene expression used in numerous cellular contexts to generate asymmetric enrichment of an encoded protein. This process has emerged as a fundamental regulatory mechanism that operates in a wide range of organisms to control an array of cellular processes. Recently, significant advancements have been made in our understanding of the mechanisms that regulate several steps in the mRNA localization pathway. Here we discuss progress made in understanding localization element recognition, paying particular attention to the role of RNA structure. We also consider the function of mRNP granules in mRNA transport, as well as new results pointing to roles for the endocytic pathway in mRNA localization.